2020
DOI: 10.1128/mbio.01110-20
|View full text |Cite
|
Sign up to set email alerts
|

Rrp6 Regulates Heterochromatic Gene Silencing via ncRNA RUF6 Decay in Malaria Parasites

Abstract: The heterochromatin environment plays a central role in silencing genes associated with the malaria parasite’s development, survival in the host, and transmission to the mosquito vector. However, the underlying mechanism regulating the dynamic chromatin structure is not understood yet. Here, we have uncovered that Plasmodium falciparum Rrp6, an orthologue of eukaryotic RNA exosome-associated RNase, controls the silencing of heterochromatic genes. PfRrp6 knockdown disrupted the singular expression of the GC-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…S3A ). We examined the changes in transcriptome upon Pfhmgb1 KO at ring, trophozoite, and schizont stages and found that most differentially expressed genes (DEGs) were structured noncoding RNAs (ncRNAs) such as tRNA, rRNA, and snoRNA and heterochromatin-associated genes ( 10 , 11 ), such as genes encoding exported proteins, variant genes of var , rifin , stevor , and Pfmc-2tm , and var -associated noncoding ruf6 genes ( 14 , 17 ) ( Fig. S3B and C and Table S1B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S3A ). We examined the changes in transcriptome upon Pfhmgb1 KO at ring, trophozoite, and schizont stages and found that most differentially expressed genes (DEGs) were structured noncoding RNAs (ncRNAs) such as tRNA, rRNA, and snoRNA and heterochromatin-associated genes ( 10 , 11 ), such as genes encoding exported proteins, variant genes of var , rifin , stevor , and Pfmc-2tm , and var -associated noncoding ruf6 genes ( 14 , 17 ) ( Fig. S3B and C and Table S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data are supportive of the speculation that the loss of PfHMGB1 releases the centromere superdomain, which, to some extent, disrupts the strictly organized centromere/telomere-dependent nuclear architecture. Such a defect may trigger alteration of local chromatin environment and gene expression, particularly for those genes which are highly dependent on the local chromatin structure, i.e., variant genes ( 13 , 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a number of upsA var loci, a special RNAse, PfRNAse II, plays a role in silencing upsA derived transcripts 19 . The concentration of ncRNA RUF6 from different loci seems to play a general role in silencing heterochromatic genes such as var, rif and others, given that the knockdown of the RNAse PfRrP6 leads to generalized derepression of heterochromatin 14 . We hypothesized that by using temporary knockdown of factors putatively participating in these events, the hierarchy of factors playing a role in maintenance or modification of epigenetic signatures of var transcription might be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The var intron found in all complete var genes appears to bi-directionally transcribe non-coding RNAs which are involved in var promoter activity 910 , although activation or silencing can also be achieved in the absence of this motif 11 . GC-rich ncRNAs seem to play a major role in the control of var gene expression 12,13 , and the exosome related RNAse PfRrP6 seems to fine-regulate the degradation of these RNAs 14 . Several proteins interact directly or indirectly with var 5' upstream regions:…”
Section: Introductionmentioning
confidence: 99%